In schlechter Verfassung? Ursachen und Konsequenzen der EU-Verfassungskrise - Beckmann, Martin; Deppe, Frank; Heinrich, Mathis (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
After the failed referenda in France and the Netherlands the European Union is in trouble. The integration process is confronted with a double crisis. Firstly the legitimacy of the EU in the population, particularly in lower income groups, has been weakened because of the negative social effects of neoliberal integration projects such as the Lisbon strategy. Secondly the EU is faced with a crisis of leadership. The Franco-German project of making the EU a global player in security policies that also rivals the US failed because of resistance of other European Governments.